2017
DOI: 10.2135/cropsci2016.09.0754
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Selected Elite CIMMYT Maize Hybrids in East and Southern Africa

Abstract: Genetic gain within the CIMMYT Eastern and Southern Africa (ESA) hybrid maize (Zea mays L.) breeding program from 2000 to 2010 was recently estimated at 0.85 to 2.2% yr−1 under various environmental conditions. Over 100 varieties were disseminated from CIMMYT to farmers in ESA, hence the need to check genetic diversity and frequency of use of parents to avoid potential narrowing down of the genetic base. Fifty‐five parents from CIMMYT ESA used in the hybrids were fingerprinted using genotyping‐by‐sequencing. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…Average genetic distance reported was 0.37 which is comparable with the earlier findings [26][27][28]. Masuka et al, [26] reported distances ranging from 0.004 to 0.40 with a mean of 0.294 from the analysis of 53 parental lines and two F 2 populations derived from the CIMMYT Africa breeding program. Beyene et al, [27] analyzed the genetic distances of 703 doubled haploids and reported distances ranging from 0.070 to 0.457 with an average of 0.355.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Average genetic distance reported was 0.37 which is comparable with the earlier findings [26][27][28]. Masuka et al, [26] reported distances ranging from 0.004 to 0.40 with a mean of 0.294 from the analysis of 53 parental lines and two F 2 populations derived from the CIMMYT Africa breeding program. Beyene et al, [27] analyzed the genetic distances of 703 doubled haploids and reported distances ranging from 0.070 to 0.457 with an average of 0.355.…”
Section: Discussionsupporting
confidence: 82%
“…For Beyene et al, [27] most of the distances fell between 0.300 to 0.475 with a frequency of 69% and in addition, less than 5% of the distances fell below 0.10. Masuka et al, [26] on the others reported 97.7% of the pairwise comparisons falling between 0.20 and 0.40 with only 0.5% showing <0.10 genetic distance. Studies however, from different geographical regions have reported relatively contrasting genetic distance like Li et al, [29] who evaluated popcorn lines from China using simple sequence repeats (SSRs) and reported genetic distances ranging from 0.125 to 0.730 with an average of 0.477.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, earlier breeders identified and composited the most productive landraces into genetically diverse populations, forming the foundation of inbred line development and pedigree breeding [ 7 ]. Modern breeding practices, in which a narrow range of inbred lines are included in crossing programs, have narrowed the genetic base of most cultivated crops, which have negatively affected the adaptability of the crop to changing climates, devastating pathogens, and insect-pests [ 8 ]. In order to provide a buffer against the possible effects of novel threats, it is essential to broaden the genetic base of breeding populations by introgressing an enlarged pool of beneficial alleles.…”
Section: Introductionmentioning
confidence: 99%
“…As a direct consequence, some newly developed maize varieties, including hybrids exhibit reduced genetic diversity [7], which may limit genetic gains and resilience to abiotic stresses. For example, by assessing the genetic diversity among selected elite CIMMYT Maize Hybrids in East and Southern Africa (ESA), Masuka et al [7] observed that repeated use of four inbred parents resulted in narrowing of the genetic base of 29 to 58% of the hybrids, which could pose major risk in case of pest or disease outbreaks that are most likely under the prevailing climate changes.The global climate over the past decade has changed rapidly, and temperatures are predicted to increase [8]. Similarly, precipitation patterns are expected to change significantly, which could adversely affect crop productivity either through drought or waterlogging [8].…”
mentioning
confidence: 99%